APLIKASI CANVA SEBAGAI MODEL DESAIN KEMASAN PADA BERBAGAI PRODUK DI PONPES AL MISBAH BOGOR - Matondang, Nurhafifah; Isnainiyah, Ika Nurlaili; Handayani, Tati; Sufyati, Sufyati; Pusporini, Pusporini (LPPM Universitas Bina Bangsa, 2025)
The growing technology affects aspects of life that depend on effective and efficient information. The educational aspect is closely related to technology where students are required to be able to operate computers and software. Islamic boarding schools are Islamic-based educational institutions that study religious sciences. Along with the times, boarding schools are required to be able to innovate by incorporating the general education curriculum into the pesantren curriculum, especially computer lessons so that students not only master religious knowledge but also recognize and add insight into technology.Therefore, the main objective of this community service activity is to provide knowledge and conduct training for Al Misbah boarding school students in honing their creativity and skills in making product label designs and brand labels. The students are expected to be able to independently create their own designs using the free Canva application. This activity is a real contribution in empowering the boarding school in promoting their own processed products with their own labels as well. This community service also has a questionnaire and provides positive feedback for the students of Al Misbah Islamic Boarding School.